2012
DOI: 10.1093/eurheartj/ehs053
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment and risk of cardiovascular events and mortality

Abstract: In people at increased CV risk, impairments on baseline cognitive testing are associated with a graded increase in the risk of stroke, congestive heart failure, and CV death, but not coronary events. An MMSE score of <24 increased CV disease risk to the same extent as a previous stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
119
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(136 citation statements)
references
References 37 publications
12
119
0
5
Order By: Relevance
“…Most recent population‐based epidemiological studies have extensively reported a consistent association between cognitive impairment and increased risk of all‐cause mortality in the elderly, and MMSE score as a common measure of cognitive impairment has been a powerful and independent predictor of all‐cause mortality 4, 7, 16, 21. To the best of our knowledge, only 2 studies have examined the relationship between baseline cognitive function and mortality in China 5, 6.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most recent population‐based epidemiological studies have extensively reported a consistent association between cognitive impairment and increased risk of all‐cause mortality in the elderly, and MMSE score as a common measure of cognitive impairment has been a powerful and independent predictor of all‐cause mortality 4, 7, 16, 21. To the best of our knowledge, only 2 studies have examined the relationship between baseline cognitive function and mortality in China 5, 6.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been suggested that cognitive impairment provides predictive value for CVD, although the underlying pathological mechanisms of any correlations are less clear 7, 8. The accumulating evidence in support of the association between cognitive impairment and CVD led to formulation of the hypothesis that MMSE score might also provide additional predictive value for CVD mortality 16.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations